A Machine Learning Approach for Rainfall and Crop Prediction to Assist Farmers in Suitable Crop Production. - Shekhawat, Aditya Singh.; Haldar, Rishin. (Tufts University. Tisch Library., 2019)
This presentation was from 6th Annual scientific Symposium in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy